The Takeover of Family Business: An Exploratory Study in Light of Sensemaking Approach (Global Journal of Management and Business Research, 2021)
The takeover of family business nowadays raises delicate issues related to power, transfer of ownership and management, to which is added the family context and all the particularities that this implies. In view of the importance of the takeover process, the main objective of this paper is to reflect on the emotional experience of the takeovers in order to understand its effect on the conduct of change and decision-making in the family business. Particular attention will first be paid to the perception of the future buyers of the change situation. An effort to understand the role of these buyers in this process will then be highlighted on the basis of the Sensemaking approach. Conclusively, by adopting a qualitative approach, we will present the results of an exploratory study conducted with a Moroccan family group operating in the hotel sector in order to better understand the takeover process.
Keywords: family business; takeover; sensemaking and change management